Acceptance of Digital Learning Tools in Higher Education: A Case Study of Microsoft Teams Application - Ahmet Kamil Kabakuş; Ekrem Bahçekapılı; Fatih Demir; Ahmet Ayaz (Trends in Business and Economics)
This study explores the adoption of Microsoft Teams within a higher education setting using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. It specifically examines how performance expectancy, effort expectancy, social influence, and facilitating conditions influence the platform's usage. Data were collected through a survey involving 143 participants and analyzed via structural equation modeling. Findings reveal that performance expectancy, social influence, and facilitating conditions significantly impact the intention to use Microsoft Teams, whereas effort expectancy does not. The results underscore that students and educators alike are more likely to adopt Microsoft Teams if it enhances their performance and productivity, if social influences (such as peer and faculty encouragement) are favorable, and if the required technological infrastructure is in place. Effort expectancy’s lack of influence suggests that users may find the platform sufficiently intuitive, thus minimizing the perceived effort required to engage with it. This insight is particularly valuable for institutions focusing on seamless user experiences. Educational institutions planning digital transformations should prioritize performance-enhancing features, support social collaboration, and ensure robust infrastructure to promote successful adoption. By aligning their strategies with user expectations and infrastructure needs, institutions can create a more conducive environment for effective digital learning.